Burden of disease due to amphetamines, cannabis, cocaine, and opioid use disorders in South America, 1990–2019: a systematic analysis of the Global Burden of Disease Study 2019 - Castaldelli-Maia, João M. (2020)
The Bill & Melinda Gates Foundation.